Pengembangan Bahan Ajar Pembelajaran Matematika Untuk Mahasiswa PGSD Semester 6 - Erna Yayuk (Scholaria: Jurnal Pendidikan dan Kebudayaan, 2019)
The purpose of this study was produce a mathematics learning companion book that was feasible to use and to measure the student's response to the teaching material. This study uses the Research and Development (R & D) method with a 4D model, which includes needs analysis, design, development, and dissemination. The feasibility was measured with the validity test from material and the design expert. The effectiveness was measured with the test to one class of PGSD FKIP UMM students, then the second test was conducted in 2 classes. The results of the research obtained are the validity values of teaching materials worthed 91.6%, and the validation test the material experts scored 78.8%, all are in ‘valid’ criteria. The effectiveness of the teaching materials were also shown from positive responses obtained from lecturers and students as product users. After revision, the effectiveness of teaching materials reached 86.93%, in the ‘effective’ criteria. Lecturers and students concluded that the use of teaching materials companion book was effective for learning